Alternative Splicing of CIPK3 Results in Distinct Target Selection to Propagate ABA Signaling in Arabidopsis - Sanyal, Sibaji K.; Kanwar, Poonam; Samtani, Harsha; Kaur, Kanwaljeet; Jha, Saroj K.; Pandey, Girdhar K. (Frontiers in Plant Science, 2017)
Calcium (Ca2+) signaling is pivotal in transmission of information in the cell. Various Ca2+ sensing molecules work to sense and relay the encrypted messages to the intended targets in the cell to maintain this signal transduction. CBL-interacting protein kinases (CIPKs) are crucial components of Ca2+ signal transduction during various abiotic stresses. Although there are intron rich CIPKs in the plant genome but very little has been reported about their alternative splicing. Moreover the physiological significance of this event in the Ca2+ signaling is still elusive. Therefore in this study, we have selected CIPK3, which has highest number of splice variants amongst Arabidopsis CIPKs. Expression profiling of five splice variants of CIPK3 by qRT-PCR in four Arabidopsis thaliana ecotypes revealed preferential transcript accumulation but similar subcellular localization of the variants and interaction with similar CBLs. ABA and drought treatment resulted in the higher accumulation of the alternately spliced transcripts of CIPK3 in Arabidopsis ecotype Wassilewkija. The transcripts of CIPK3.1 and CIPK3.4 are relatively more induced compared to other alternative splice variants. Out of four splice variants studied, we found CIPK3.1 and CIPK3.2 showing preference for ABR1, a previously reported interactor of CIPK3. We conclude that the differential expression and choice of downstream partner by CIPK3-splice variants might be one of the mechanisms of Ca2+ mediated preferential regulation of ABA and other stress signals.